Virtual Science Laboratory (Vislab): The Effect of Visual Signalling Principles towards Students’ Perceived Motivation - Ai Chin, Wong; Ahmad Jaafar Wan Yahaya, Wan; Muniandy, Balakrishnan (International Journal of Engineering and Technology, 2018)
The purpose of this study is to investigate the effect of Virtual Science Laboratory (ViSLab) on visual signalling principles towards studentsâ€™ perceived motivation. Motivation can be identified as a dimension that determines learning success and causes the high failure rate among online learners, especially in VR environments. Cognitive load researchers need to determine the motivational effects of instructional conditions, and identify strategies that maintain studentsâ€™ awareness of the learning materials without their being distracted by the world outside, as well as help out instructional designers to distinguish the power of VR learning environments in enhancing the motivation of learners. The lesson of the science laboratory safety is developed in two different modes, Virtual Reality with Signalling (VRS) and Virtual Reality Non Signalling (VRNS). 2x2 quasi experimental factorial design is adopted in this research. The independent variables were the two modes of presentation. The moderator variable is the spatial ability. The dependant variable is the perceived motivation. The study sample consisted of 141 students. The Instructional Material Motivational Scale (IMMS) from Keller was used to determine studentsâ€™ perceived motivation. ANOVA was carried out to determine if a significant difference occurred between the two groups in their motivation towards instructional materials. The findings of this study showed that the use of Virtual Reality with Signalling (VRS) treatment mode helped pupils perform significantly better than Virtual Reality Non Signalling (VRNS) in learning science laboratory safety. Overall, visual signalling principle needs to be considered in the design and development of Virtual Science Laboratory (ViSLab) to promote more effective learning.Â Â